Role of the Article XX of the general tariffs and trade agreement in international trade - Т. Фу; К.Ж. Алтаева; А.Б. Сманова; Ш.Қ. Ергөбек (Хабаршы. Заң сериясы, 2021)
This article examines the environmental exceptions in Article XX of the General Agreement on Tariffs and Trade (GATT) and analyzes the illegible or unclear content of the articles so that environmental provisions can be applied to current international environmental issues. GATT Article XX is the most important environmental clause in the GATT / WTO. This article states that under certain circumstances, a country’s laws or measures may deviate from multilateral trade rules. These exclusions include clause (b): “necessary to protect human, animal or plant life or health”; and (g): “relating to the conservation of exhaustible natural resources if such measures are made effective in conjunction with restrictions on domestic production or consumption.” The provisions of Article XX did not contain a clear concept of environmental protection during the development. As environmental awareness increases in the international community, the WTO is gradually focusing on environmental issues in trade, and Article XX plays an increasingly important role. Although the wording of the articles has not been changed, the interpretation of the meaning of the articles is constantly evolving. In specific cases, the existing legal loopholes in Article XX were analyzed and the prospects for their development were predicted. The study concluded that, in practice, the WTO Dispute Settlement Body, on the one hand, expands the scope of Article XX (b) and (g) to meet environmental protection requirements, on the other hand, through flexible preamble control, it is possible to prevent the impact of environmental protection measures on normal trade. Key words: Article XX of the GATT, environmental protection, general exceptions, WTO.